Thermally conductive silicone composition and cured product thereof

By using organohydrogen polysiloxane with specific structures and hydrosilylation catalysts in the heat-conducting silicone composition, the problems of rising viscosity and increasing thermal resistance are solved, and the thermally conductive silicone composition with excellent flexibility and small changes in thermal resistance are achieved and the cured product thereof is achieved.

CN119907831APending Publication Date: 2025-04-29FUKOKU CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380070901.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-04
Filing Date
2023-02-07
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

While the existing heat-conducting silicone compositions increase the viscosity while increasing the heat conductivity, resulting in a decrease in adhesion and an increase in thermal resistance. The increased hardness of the cured product will reduce the impact absorption capacity and the expansion stress relief effect.

Method used

The number of residual reactive functional groups is reduced by using organohydrogen polysiloxanes with silicon atoms bonded to hydrogen atoms at the end of the molecular chain in the heat-conducting silicone composition to improve flexibility and reduce thermal resistance changes.

Benefits of technology

The thermally conductive silicone composition with excellent flexibility and small thermal resistance changes are achieved and its cured product is improved, the thermal coupling efficiency between the heat generator and the heat dissipation body is improved, and the hardness and thermal resistance of the cured product are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119907831A_ABST
    Figure CN119907831A_ABST
Patent Text Reader

Abstract

A curable thermally conductive silicone composition which is a liquid silicone and contains: (A-1) an organopolysiloxane having an alkenyl group at each of both ends of a molecular chain; (A-2) an organopolysiloxane having an alkenyl group at one end of the molecular chain and not having a reactive functional group at the other end; (A-3) an organopolysiloxane having at least three alkenyl groups in the molecule; (A-4) an organohydrogen polysiloxane which has a silicon atom-bonded hydrogen atom at the molecular chain end and does not have a silicon atom-bonded hydrogen atom at the molecular chain side chain; (B) a hydrosilylation catalyst; and (C) a thermally conductive filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermally conductive silicone composition and a cured product thereof. Background Art

[0002] In recent years, the miniaturization and high integration of electrical and electronic components have been continuously promoted, and the heat generation has gradually increased. Similarly, in secondary batteries, their capacity and output power are gradually increasing, and the heat generation is also increasing. For heating elements such as electrical components, electronic components, and secondary batteries, it is necessary to prevent their temperature from rising excessively, so a structure is adopted to dissipate the heat generated in the heating element to a heat sink such as a radiator or an outer packaging shell. The heat-conductive composition or its solidified product is sandwiched between the heating element and the heat sink to improve the thermal coupling between the heating element and the heat sink, and is used to efficiently transfer the heat from the heating element to the heat sink. As a heat-conductive composition or its solidified product, there are various forms of products such as heat dissipation grease and heat sinks on the market. Among them, the heat-conductive composition and its solidified product, which are called caulking agents, are liquid when applied to the heating element and the heat sink, and have excellent followability to unevenness (i.e., gap filling) and can achieve precise coating, and solidify over time, thereby preventing the occurrence of pumping and dripping, and are therefore widely used.

[0003] In order to improve the heat dissipation performance by sandwiching a heat-conducting composition or its cured product between the heating element and the radiator, it is first important that the heat-conducting composition and its cured product have high thermal conductivity. In order to improve the thermal conductivity, a heat-conducting filler with high thermal conductivity is mixed into the heat-conducting composition. In addition, in order to improve the heat dissipation characteristics, it is also important to reduce the thermal resistance at the interface between the heating element and the heat-conducting composition or its cured product, and the interface between the radiator and the heat-conducting composition or its cured product. However, when the mixing ratio of the heat-conducting filler is increased in order to obtain high thermal conductivity, the viscosity of the mixed material of the heat-conducting composition increases, and as a result, the closeness of the heat-conducting composition, its cured product, the heating element and the radiator when in contact decreases, and the thermal resistance at the interface increases. If the mixing ratio of the heat-conducting filler is increased, the hardness of the cured product of the heat-conducting composition also increases. If the hardness of the cured product is high, not only the impact absorption capacity is reduced, but also the effect of relieving the stress caused by expansion and contraction due to temperature changes is reduced, and the mechanical impact applied to the electrical components, electronic components, and secondary batteries as the heating element becomes larger.

[0004] When the heat conductive composition and its cured product contain volatile components or generate gas due to a chemical reaction that progresses over time, tiny gaps are generated at the interface with the heating element or the heat dissipating element, or bubbles are generated inside the heat conductive composition and its cured product. Due to the generation of gaps and bubbles, the heat conductive composition and its cured product have difficulty in transferring heat.

[0005] As a representative example of a thermally conductive composition called a gap filler, there is a thermally conductive composition that uses liquid, i.e., uncured silicone as a matrix and mixes a thermally conductive filler or the like into the matrix. For example, Patent Document 1 discloses a thermally conductive silicone gel composition containing (A) an alkenyl-containing organopolysiloxane, (B) a linear organohydrogenpolysiloxane, (C) a catalyst for a hydrosilylation reaction, and (D) a thermally conductive filler. The thermally conductive filler is surface-treated with an alkoxysilane having an alkyl group with 6 or more carbon atoms in the molecule, thereby making it possible to reduce the viscosity of the thermally conductive silicone gel composition even when the amount of the thermally conductive filler added is increased to improve thermal conductivity, thereby achieving precise coating while improving gap filling properties. If a low molecular weight polydimethylsiloxane is used to reduce the viscosity, the crosslinking density during curing becomes high and the cured product becomes hard. However, in the thermal conductive silicone composition described in Patent Document 1, an organohydrogen polysiloxane containing an average of 2 to 4 silicon-bonded hydrogen atoms in the molecule and at least 2 of them in the side chain of the molecular chain is used as a linear organohydrogen polysiloxane. By using such a linear organohydrogen polysiloxane as a crosslinking extender, the entire composition is slowly crosslinked, and a thermal conductive silicone gel composition that forms a gel-like cured product can be obtained.

[0006] For example, in a thermally conductive composition in which a thermally conductive filler is mixed into a matrix containing a polymer compound, the thermal conductivity can be greatly improved by making the thermally conductive fillers contact each other in the matrix to form a thermally conductive path that does not pass through the matrix. In the case of using spherical fillers as thermally conductive fillers and mixing thermally conductive fillers of a single particle size into the matrix, the number of locations where the thermally conductive fillers contact each other cannot be increased, and there are also limitations in improving the thermal conductivity. Patent document 1 discloses a method of mixing and adding thermally conductive fillers of large particle size and small particle size in a ratio according to the closest packing theoretical distribution curve. Patent document 2 discloses a thermally conductive silicone gel composition in which two types of thermally conductive fillers with different median diameters (D50) are mixed in an appropriate ratio and then mixed into a matrix, using the median diameter (D50) of the particle size corresponding to 50% in the cumulative particle size distribution based on a volume basis to represent the particle size of the thermally conductive filler. In a thermally conductive silicone gel composition to which thermally conductive fillers of different particle sizes are mixed and added, the thermally conductive fillers are distributed in the matrix in a state of near-closest packing, with small-particle-size thermally conductive fillers existing between large-particle-size thermally conductive fillers, and the number of sites where the thermally conductive fillers are in contact with each other is significantly increased, thereby being able to obtain a high thermal conductivity while maintaining high flexibility and a low dielectric constant.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: International Publication No. 2019 / 021824

[0010] Patent Document 2: Japanese Patent No. 6938808

[0011] Non-patent literature

[0012] Non-patent document 1: Jong-Woo, et al., "The properties of AlN-filled epoxy molding compounds by the effects of filler size distribution", J. Mater. Sci., 35, 5907-5913 (2000) Summary of the invention

[0013] Problems to be solved by the invention

[0014] According to the techniques described in Patent Documents 1 and 2, a thermally conductive silicone gel composition having excellent flexibility can be obtained. However, in the thermally conductive silicone gel composition described in Patent Document 1, the silicon-bonded hydrogen atoms in the side chains of the molecular chains of the linear organic hydrogen polysiloxane molecules react with the alkenyl groups of the alkenyl-containing organic polysiloxane due to the crosslinking reaction. Due to the steric hindrance of the molecules, the reaction can only be carried out incompletely, and silicon-bonded hydrogen atoms may remain after the crosslinking reaction is completed. The remaining silicon-bonded hydrogen atoms react with water, alcohol, etc. over time and are freed in the form of hydrogen gas. Due to the hydrogen gas, bubbles are generated inside the cured product obtained by curing the thermally conductive silicone gel composition, or gaps are generated at the interface with the heating element and the heat sink. As a result, it is difficult to transfer heat between the heating element and the heat sink due to the increase in thermal resistance.

[0015] In addition, although Patent Document 2 provides a method of adding two types of thermally conductive fillers distinguished by median diameter (D50) to the matrix at a given ratio, the range of particle size distribution in the thermally conductive filler is not considered. Even if the median diameter (D50) is the same, as long as the particle size distribution is different, the particle size distribution after mixing will be different when the two types of thermally conductive fillers specified by the median diameter (D50) are mixed at a prescribed ratio, and the thermally conductive filler cannot be distributed in the matrix in a state close to the densest filling. As a result, the viscosity of the thermally conductive silicone gel composition increases, and the hardness of its cured product increases. If the viscosity increases, not only the filling property decreases, but also the processability deteriorates, and the adhesion with the heating element and the heat sink decreases, which increases the thermal resistance. In addition, if the hardness of the cured product increases, when it is impacted, it will transmit the impact to the electronic substrates such as the ECU (Electronic Control Unit, electronic control unit), the electronic components such as the CPU (Central Processing Unit, central processing unit), and the secondary battery as the heating element, causing damage to the heating element.

[0016] An object of the present invention is to provide a thermally conductive silicone composition having excellent flexibility and little change in thermal resistance over time, and a cured product thereof.

[0017] Means for solving problems

[0018] According to one embodiment of the present invention, the thermally conductive silicone composition comprises:

[0019] (A-1) an organopolysiloxane having alkenyl groups at both ends of the molecular chain;

[0020] (A-2) an organopolysiloxane having an alkenyl group at one end of the molecular chain and having no reactive functional group at the other end;

[0021] (A-3) an organopolysiloxane having at least three alkenyl groups in the molecule;

[0022] (A-4) an organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at the molecular chain terminals and no silicon-bonded hydrogen atoms at the molecular chain side chains;

[0023] (B) a hydrosilylation catalyst; and

[0024] (C) Thermally conductive fillers,

[0025] The thermally conductive silicone composition is in liquid form and has curability.

[0026] According to another aspect of the present invention, the cured product is a cured product obtained by curing the thermally conductive silicone composition described above by a hydrosilylation reaction.

[0027] Effects of the Invention

[0028] According to the present invention, a thermally conductive silicone composition having excellent flexibility and little change in thermal resistance over time and a cured product thereof can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram illustrating the heat transfer path in the thermally conductive silicone composition.

[0030] Figure 2 This is a graph showing the relationship between the particle size of the thermally conductive filler and the cumulative frequency.

[0031] Figure 3 This is a graph showing the relationship between the particle size of the thermally conductive filler and the cumulative frequency.

[0032] Figure 4 This is a graph showing the relationship between the particle size of the thermally conductive filler and the cumulative frequency. DETAILED DESCRIPTION

[0033] Below, the method for implementing the present invention is described. The thermally conductive silicone composition based on the present invention is sandwiched between the heating element and the heat sink in its original state (uncured) or in a cured state to improve the thermal coupling between the heating element and the heat sink. As the heating element, for example, electronic substrates such as ECU, electronic components such as CPU, secondary batteries, etc. can be exemplified, and as the heat sink, for example, radiators, outer packaging shells, etc. can be exemplified. In the thermally conductive silicone composition used in these heat dissipation components, thermally conductive fillers are added to improve thermal conductivity, but it is expected that even if the amount of thermally conductive fillers added is increased, the flexibility is large and the change in thermal resistance over time is small. The inventors have studied the conditions for obtaining a thermally conductive silicone composition having such characteristics. As a result, it was found that by reducing the cross-linking extension in the matrix containing silicone and reducing the residual reactive functional groups, the flexibility of the thermally conductive silicone composition and its cured product is improved, and the change in thermal resistance over time is reduced.

[0034] Generally speaking, a heat-conductive silicone composition uses a composition obtained by mixing an organopolysiloxane having an alkenyl group and an organohydrogenpolysiloxane having a silicon-bonded hydrogen atom in the side chain of the molecular chain as a liquid silicone serving as a matrix. The liquid silicone undergoes a hydrosilylation reaction in the presence of a catalyst to promote crosslinking and become a cured product. In order to reduce the viscosity of the heat-conductive silicone composition, it is necessary to reduce the viscosity of the liquid silicone serving as the matrix. To reduce the viscosity of the liquid silicone, it is necessary to use a liquid silicone with a small molecular weight. However, if a liquid silicone with a small molecular weight is crosslinked, the crosslinking density becomes high and the hardness of the cured product becomes high. On the other hand, in order to reduce the hardness of the cured product while using a low molecular weight liquid silicone, it is necessary to add a large amount of an organohydrogenpolysiloxane having a silicon-bonded hydrogen atom in the molecule to extend the molecular chain. However, in this case, the amount of silicon-bonded hydrogen atom relative to the alkenyl group becomes large. In addition, the silicon-bonded hydrogen atom present in the side chain of the molecular chain of the organohydrogenpolysiloxane cannot react completely due to steric hindrance and is also easy to remain after curing. Due to these factors, when the ratio of the organohydrogenpolysiloxane in the liquid silicone is increased, a large amount of silicon-bonded hydrogen atoms remain even after curing by cross-linking.

[0035] The silicon-bonded hydrogen atoms that remain after curing react with water or alcohol in the presence of a catalyst to generate hydrogen gas, thereby generating gaps at the interface with the heating element or the heat sink in the cured product, or generating bubbles inside the cured product. In addition, the number of gaps and bubbles caused by the remaining silicon-bonded hydrogen atoms increases over time, so the thermal resistance of the cured product also increases over time. Therefore, in the thermally conductive silicone composition based on the present invention, by using an organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at the ends of the molecular chain and no silicon-bonded hydrogen atoms at the side chains of the molecular chain, the reactivity of the organohydrogenpolysiloxane to alkenyl groups is improved, and the silicon-bonded hydrogen atoms that remain after curing are reduced, thereby suppressing the change in thermal resistance over time even when the amount of the organohydrogenpolysiloxane is increased to improve flexibility.

[0036] Therefore, the thermally conductive silicone composition according to the present invention contains the following four polymers as liquid silicone:

[0037] (A-1) an organopolysiloxane having alkenyl groups at both ends of the molecular chain;

[0038] (A-2) an organopolysiloxane having an alkenyl group at one end of the molecular chain and having no reactive functional group at the other end;

[0039] (A-3) an organopolysiloxane having at least three alkenyl groups in the molecule; and

[0040] (A-4) an organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at the molecular chain terminals and having no silicon-bonded hydrogen atoms at the molecular chain side chains, comprising:

[0041] (B) a hydrosilylation catalyst; and

[0042] (C) Thermally conductive fillers,

[0043] The thermally conductive silicone composition is in a liquid state and has curability. Hereinafter, main components constituting the thermally conductive silicone composition will be described.

[0044] <Liquid silicone (silicone oil)>

[0045] The liquid silicone constituting the thermally conductive silicone composition comprises four polymer components (A-1) to (A-4). Component (A-1) is an organopolysiloxane having alkenyl groups at both ends of the molecular chain, and is a base polymer of the liquid silicone.

[0046] The component (A-2) is an organopolysiloxane having an alkenyl group at one end of the molecular chain and having no reactive functional group at the other end. The polymer has an alkenyl group that is the subject of the hydrosilylation reaction at one end of the molecular chain and has no reactive functional group at the other end, so that only one end is cross-linked and the other end can move freely. By including the component (A-2) in the liquid silicone in this way, the degree of cross-linking can be reduced while suppressing bleeding, and a soft thermally conductive silicone composition can be obtained. In addition, the amount of the component (A-2) added is preferably 10 to 90 parts by mass in 100 parts by mass of the liquid silicone. If the amount added is less than 10 parts by mass, the effect of reducing the hardness of the cured product is insufficient. If the amount added is more than 90 parts by mass, the degree of cross-linking when the liquid silicone is cured by the hydrosilylation reaction becomes too low and difficult to cure. It should be noted that as the reactive functional group mentioned here, alkenyl groups, silicon-bonded hydrogen atoms, silanol groups, amino groups, etc. can be exemplified.

[0047] The component (A-3) is an organopolysiloxane having an average of at least 3 alkenyl groups in the molecule, and reacts with hydrogen atoms bonded to silicon atoms to function as a crosslinking point. The components (A-1) and (A-2) are chain polymers, and the component (A-3) may be a chain polymer or a cyclic polymer, or may have a branched structure. Examples of the component (A-3) include cyclic polymers such as 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, and straight-chain dimethyl silicone oil having 4 vinyl groups in the side chain or at the end. The component (A-3) may exist in the liquid silicone without forming a complex, or may exist in the form of a platinum complex such as a platinum (0)-2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane complex. In addition, a non-complex type component (A-3) and a complex type component (A-3) may coexist in the liquid silicone. The amount of component (A-3) added is preferably 0.01 to 2 parts by mass based on 100 parts by mass of the liquid silicone. If the amount of component (A-3) added is less than 0.01 parts by mass, the number of crosslinking points is too small and curing does not proceed. On the contrary, if the amount of component (A-3) added is more than 2 parts by mass, the number of crosslinking points is too large and the hardness of the cured product is too high.

[0048] The component (A-4) is an organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at the ends of the molecular chain and having no silicon-bonded hydrogen atoms at the side chains of the molecular chain, and is a polymer component that reacts with each of the polymer components (A-1) to (A-3). The component (A-4) is a chain polymer that may or may not have a branched structure. Examples of the component (A-4) include a straight-chain organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at both ends of the molecular chain and having no silicon-bonded hydrogen atoms at the side chains of the molecular chain; an organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at the ends of the molecular chain but having no silicon-bonded hydrogen atoms at the side chains of the molecular chain and having a branched structure, etc. By using the component (A-4), the polymer of the component (A-1) can be extended by a hydrosilylation reaction, and even when a low-viscosity alkenyl-containing organopolysiloxane is used, a cured product with low hardness can be obtained as a cured product of the thermally conductive silicone composition. In addition, since the silicon-bonded hydrogen atoms in the component (A-4) are present at the ends of the molecular chain rather than in the side chains of the molecular chain, it is not easy for the reactivity to be reduced due to steric hindrance, and it is not easy for unreacted silicon-bonded hydrogen atoms to remain in the cured product. In particular, it is preferred to add the component (A-4) so ​​that the silicon-bonded hydrogen atoms contained in the component are 0.6 to 1.6 moles relative to 1 mole of alkenyl groups in the liquid silicone. If the amount of silicon-bonded hydrogen atoms relative to 1 mole of alkenyl groups is less than 0.6 moles, no curing will occur. On the other hand, if it is greater than 1.6 moles, the remaining silicon-bonded hydrogen atoms increase, and the amount of hydrogen gas generated by the reaction with water, alcohol, etc. in the presence of a catalyst increases.

[0049] It should be noted that the liquid silicone used in the thermally conductive silicone composition of the present invention may contain an organopolysiloxane represented by the following formula (1) as a component (A-5) in addition to the polymer containing the above-mentioned components (A-1) to (A-4). Since the component (A-5) does not have reactive functional groups such as alkenyl groups and silicon-bonded hydrogen atoms, it can reduce the crosslinking density when the liquid silicone is cured, thereby reducing the hardness of the cured product. The addition amount of the component (A-5) is preferably 0% by mass or more and 80% by mass or less in the liquid silicone. If the addition amount of the component (A-5) is greater than 80% by mass, the crosslinking density is too low and the shape cannot be maintained.

[0050] [Chemistry 1]

[0051]

[0052] The viscosity of the liquid silicone containing each component (A-1) to (A-4) or the liquid silicone containing each component (A-1) to (A-5) is preferably 10 to 10000 mPa·s. If the viscosity is less than 10 mPa·s, the thermally conductive filler is likely to settle during storage of the thermally conductive silicone composition, and if the viscosity is greater than 10000 mPa·s, the viscosity of the thermally conductive silicone composition increases, and the adhesion of the thermally conductive silicone composition and its cured product to the heating element or the heat dissipating element deteriorates.

[0053] <Hydrosilylation catalyst>

[0054] In order to promote the crosslinking reaction in the liquid silicone described above, a hydrosilylation catalyst as component (B) is added to the thermally conductive silicone composition. Examples of the hydrosilylation catalyst include metal-containing catalysts such as platinum-based catalysts, rhodium-based catalysts, and palladium-based catalysts. More specifically, examples include platinum (0)-2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane complexes and platinum (0)-1,3-divinyltetramethyldisiloxane complexes. One of these catalysts may be used alone, or two or more catalysts may be used in combination. The content of the hydrosilylation catalyst in the thermally conductive silicone composition may be a so-called catalytic amount. As a specific example, it is preferably 0.1 to 1500 ppm relative to the liquid silicone in terms of the mass of the metal element contained in the catalyst. The amount of the hydrosilylation catalyst added may be appropriately adjusted to obtain the desired curing speed.

[0055] <Thermal conductive filler>

[0056] The thermally conductive filler as component (C) is used to impart thermal conductivity to the thermally conductive silicone composition and its cured product. As the thermally conductive filler, for example, metals, alloys, metal oxides, metal hydroxides, metal nitrides, metal carbides, etc. are used. One of these substances may be used alone, or two or more of them may be used in combination. From the viewpoint of reducing the viscosity of the thermally conductive silicone composition, the shape of the thermally conductive filler is preferably not any one of a plate-like, needle-like, and fibrous shape, and is preferably a spherical or approximately spherical shape. The thermally conductive filler is preferably formed of a soft material, and the Mohs hardness of the thermally conductive filler is preferably low. If the Mohs hardness becomes higher, the thermally conductive filler will scrape the inner surface of the sizing machine used in the coating of the thermally conductive silicone composition and the mixing device used in the mixing, resulting in the problem that foreign matter is easily mixed into the thermally conductive silicone composition or the maintenance frequency of the device becomes higher. As materials with a low Mohs hardness and suitable for use as thermally conductive fillers, for example, aluminum hydroxide (Mohs hardness 3) and zinc oxide (Mohs hardness 5) can be cited. Regarding the amount of thermally conductive filler added to the thermally conductive silicone composition, the volume percentage of the thermally conductive filler in the thermally conductive silicone composition is preferably in the range of 68.0 volume % to 75.0 volume %. The volume percentage of the thermally conductive filler is more preferably 69.5 volume % to 75.0 volume %, and further preferably 69.5 volume % to 73.0 volume %. If the volume percentage of the thermally conductive filler is less than 68.0 volume %, the viscosity of the thermally conductive silicone composition and the hardness of its cured product decrease, but the thermal conductivity is not sufficiently high. On the other hand, if the volume percentage is greater than 75.0 volume %, the thermal conductivity of the thermally conductive silicone composition and its cured product increases, but the viscosity of the thermally conductive silicone composition and the hardness of its cured product increase.

[0057] In the thermally conductive silicone composition according to the present invention, particles of the thermally conductive filler dispersed in the liquid silicone as a matrix are in contact with each other to form a heat conduction path that does not pass through the matrix, thereby achieving high thermal conductivity. Therefore, in order to improve thermal conductivity, it is preferred not to use a thermally conductive filler of a single particle size, but to mix thermally conductive fillers of different particle sizes and add them to the liquid silicone as described in Patent Documents 1 and 2. It is known that by optimizing the particle size and addition ratio in such a way that the gaps surrounded by large-diameter particles are filled with small-diameter particles and the gaps surrounded by small particles are filled with even smaller micro-diameter particles, the filling rate of the thermally conductive filler can be increased while reducing the viscosity and hardness. Figure 1 An example of a heat transfer path in a thermally conductive silicone composition is shown. Figure 1 (a) shows an example in which a heat conductive filler 12 having a single particle size and a relatively large particle size is blended into a matrix 11. Figure 1(b) shows an example in which three types of thermally conductive fillers 12 to 14 each having a single particle size are blended into a matrix 11 : a thermally conductive filler 12 having a relatively large particle size, a thermally conductive filler 13 having a relatively small particle size, and a thermally conductive filler 14 having a very small particle size. Figure 1 The curve with arrows in the figure indicates the heat transfer path. It can be seen that by mixing and adding the heat conductive fillers 12 to 14 with different particle sizes, the heat transfer path is diversified and the thermal resistance is reduced.

[0058] Various studies have been conducted on the preferred mixing ratio of thermally conductive fillers with different particle sizes, but all of them assume that the particles are particles of a single particle size, or only use the average particle size to discuss the optimization of the particle size and the addition ratio. However, for commercially available thermally conductive fillers, the particle size is not single, but there is a range in the particle size distribution. Moreover, depending on the type of particles and the manufacturing method, the particle size distribution is different even for the same average particle size. Therefore, if only the addition ratio of each average particle size is studied, it is impossible to reduce the hardness of the cured product while making the viscosity of the thermally conductive silicone composition sufficiently low. In particular, when the amount of thermally conductive filler added is increased in order to improve thermal conductivity, it is difficult to achieve low viscosity and low hardness. Therefore, the inventors focused on the particle size distribution after mixing a plurality of thermally conductive fillers with different particle sizes, and studied the optimal particle size distribution of the thermally conductive filler in the thermally conductive silicone composition. The following is an explanation of the inventors' research results.

[0059] In order to improve the thermal conductivity of the thermally conductive silicone composition while reducing the viscosity and hardness, it is important to properly control the particle size distribution in the thermally conductive filler so that small particles enter the gaps between large-diameter particles to form a structure close to the closest packing. Non-patent document 1 discloses that for aluminum nitride (AlN) filler mixed into epoxy resin, a high filling rate close to the closest packing can be achieved by setting the addition ratio of large-diameter particles to small-diameter particles to 0.735:0.265 on a volume basis. Since the aluminum nitride filler mixed into the epoxy resin is the same as the thermally conductive filler mixed into the liquid silicone in terms of achieving a state close to the closest packing, it is considered to mix large-diameter particles and small-diameter particles at a volume ratio of 0.735:0.265.

[0060] Figure 2The broken line A in the middle represents the cumulative frequency of the particle size when particles of a single particle size of 10 μm and particles of a single particle size of 1 μm are mixed in a volume ratio of 0.735:0.265. In addition, the broken line B represents the cumulative particle size distribution when particles of single particle sizes of 50 μm, 5 μm and 0.5 μm are mixed in a volume ratio of 0.735:0.265 for particles of 50 μm and 0.735:0.265 for particles of 5 μm and 0.5 μm, respectively. However, even if the average particle size is used to identify the type of particles, the actual particles show a particle size distribution with a certain degree of fluctuation. Even if a plurality of thermal conductive fillers with different average particle sizes are simply mixed in the above ratio, it is difficult to obtain a thermal conductive filler having a certain average particle size. Figure 2 The thermally conductive silicone composition with a cumulative particle size distribution represented by broken lines A and B.

[0061] Therefore, the present inventors focused on the fact that, when the cumulative frequency on a volume basis is y (%) and the particle size is x (μm), a can be set as a positive parameter (coefficient) and the equation (2) can be used to roughly approximate Figure 2 The cumulative particle size distribution represented by the broken lines A and B. Figure 2 The curves indicated by the dashed lines in are approximate curves expressed by equation (2) when the parameter (coefficient) a is set to various values. Equation (2) can be considered to be an equation expressing the optimal cumulative particle size distribution corresponding to the closest packing.

[0062] [Mathematical formula 1]

[0063]

[0064] In formula (2), ax 1 / 2 When ≥100, y=100% because the maximum value of the cumulative particle size distribution is 100%. Figure 2 As shown, if a is increased, the approximate curve of formula (2) moves toward the smaller particle size side, and if a is decreased, it moves toward the larger particle size side. By mixing thermally conductive fillers of different average particle sizes so that the particle size distribution is as close as possible to formula (2), a thermally conductive silicone composition having high thermal conductivity and low viscosity can be obtained, and by curing such a thermally conductive silicone composition, a cured product having high thermal conductivity and low hardness can be obtained. The cumulative particle size distribution on a volume basis after mixing a plurality of thermally conductive fillers can be calculated for each type of thermally conductive filler based on the particle size distribution of the thermally conductive filler and the mixing ratio of these thermally conductive fillers.

[0065] When a plurality of heat conductive fillers are mixed in practice, it is preferred to introduce an index showing the extent to which the actual cumulative particle size distribution of the mixed heat conductive filler deviates from the cumulative particle size distribution represented by formula (2), and it is preferred to set the mixing ratio of the heat conductive filler in such a way that the deviation represented by the index is as small as possible. As an index showing the degree of deviation in the cumulative particle size distribution, the mean square error E is an effective index. When considering the cumulative particle size distribution, the particle size as the starting point (minimum value) of the cumulative frequency calculation is set to P (μm), and the particle size as the end point (maximum value) is set to Q (μm) (where Q>P), k is set to a constant satisfying k>1, and is set to 1≤n≤R (n is an integer), so as to satisfy the following formulas (3) and (4), and R particle sizes {x n}.

[0066] x n =k n-1 P, (3)

[0067] x R =Q (4)

[0068] Obviously, the particle size {x n} is a value obtained by determining R particle diameters in a relationship of forming a geometric progression with a common ratio of k between the particle diameter P as the starting point and the particle diameter Q as the end point, including the starting point and the end point, and is a calculation point of the cumulative frequency.

[0069] Furthermore, the particle size x n The actual cumulative frequency of the heat transfer filler at n (%), substitute x in equation (2) into x n The cumulative frequency is set as y n , the mean square error E is determined as shown in the following formula (5).

[0070] [Mathematical formula 2]

[0071]

[0072] It can be said that the larger the mean square error E, the greater the deviation between the actual particle size distribution of the heat conductive filler and the particle size distribution expressed by equation (2), and the smaller E, the smaller the deviation. In practice, since the mean square error E is a quadratic function of the parameter (coefficient) a, the minimum value of the mean square error E when the parameter (coefficient) a is changed can be obtained, and this minimum value is set as E min , will be the minimum value E min The value of the corresponding parameter (coefficient) a is set to a0.

[0073] According to the research of the present inventor, when 0≤E minWhen a plurality of heat-conductive fillers are combined in a manner such that the conditions of ≤45 and 5.7≤a0≤13.0 are met, a heat-conductive silicone composition with low viscosity and low hardness of the cured product can be obtained. min When a0 is greater than 45, the deviation from the ideal particle size distribution represented by formula (2) becomes larger, so the viscosity of the thermally conductive silicone composition increases and the hardness of its cured product also increases. When a0 is less than 5.7, the particle size distribution is excessively biased toward the larger particle size side. Therefore, when the thermally conductive silicone composition is sandwiched between the heating element and the heat sink, the distance between the heating element and the heat sink increases, and the heat transfer efficiency deteriorates. On the other hand, if a0 is greater than 13.0, the particle size distribution is excessively biased toward the smaller particle size side. Therefore, the surface area of ​​the thermally conductive filler increases and the viscosity of the thermally conductive silicone composition increases. Formulas (2) to (5) are derived only based on the particle size distribution of the thermally conductive filler. E described here min The optimal ranges of E and a0 are applicable regardless of the type of thermally conductive filler. Therefore, in the thermally conductive silicone composition according to the present invention, the particle size distribution of the thermally conductive filler is preferably min and a0 satisfies 0≤E min The conditions of ≤45 and 5.7≤a0≤13.0. The type of thermally conductive filler used may be one, or two or more types may be mixed and used, or two or more types of thermally conductive fillers of different materials may be mixed.

[0074] As an example, when the particle size P at the starting point of the particle size distribution of the thermally conductive filler is set to 0.010 μm, the particle size Q at the end point is set to 316 μm, and R is set to 46, k is obtained according to equations (3) and (4) to obtain k≈1.259. The particle size range is set to 0.010 μm to 316 μm here because if the particle size is too small, the specific surface area of ​​the thermally conductive filler is too large, which increases the viscosity of the thermally conductive silicone composition. If the particle size is too large, the thickness of the thermally conductive silicone composition during coating is too large, which increases the thermal resistance. R can be appropriately determined based on the accuracy required by the difference between the actual cumulative particle size distribution and the cumulative particle size distribution based on equation (2). If R is increased, the accuracy becomes better, but the amount of calculation increases. If R is reduced, the amount of calculation can also be reduced, but the accuracy slightly deteriorates.

[0075] Figure 3 This is a diagram for explaining the difference between the actual particle size distribution of the thermally conductive filler and the particle size distribution represented by equation (2) when considering the cumulative particle size distribution, when the starting particle size P is 0.010 μm, the ending particle size Q is 316 μm, and R is 46. Figure 3 In the figure, the solid curve represents the actual particle size distribution, and the dashed curve represents the particle size distribution shown in equation (2). The lengths of the line segments between the two curves and extending in the vertical direction are |y n -c n |. Figure 4This shows how the relationship between the particle size distribution calculated based on equation (2) and the actual particle size distribution changes when the value of parameter (coefficient) a is changed. Figure 4 As shown in Figure 2, the actual particle size distribution when a=9.6 is consistent with the particle size distribution based on formula (2). Figure 4 It can be seen that when a=5 and a=15, the actual particle size distribution deviates greatly from the particle size distribution based on the formula (2).

[0076] <Surface treatment agent for thermally conductive filler>

[0077] For the thermally conductive filler as component (C), in order to improve the wettability with the liquid silicone as the matrix, the surface can be hydrophobized by using a surface treatment agent. By improving the wettability with the liquid silicone, the thermally conductive filler can be dispersed in the liquid silicone with a high degree of dispersion, and the viscosity of the resulting thermally conductive silicone composition becomes lower, and the hardness of its cured product also becomes lower. Examples of the surface treatment agent used for the thermally conductive filler include alkoxysilanes having an alkyl group with more than 6 carbon atoms in the molecule such as octyltriethoxysilane and decyltrimethoxysilane, polyorganosiloxanes having a hydroxyl group in the molecule, polyether-modified silicone oil, polyglycerol-modified silicone oil, fatty acid glyceride, fatty acid sorbitan ester, fatty acid with more than 6 carbon atoms, and the like.

[0078] <Other additives>

[0079] The liquid silicone constituting the thermally conductive silicone composition may contain a curing retardant, a pigment, etc. as necessary.

[0080] <Method for producing thermally conductive silicone composition and cured product thereof>

[0081] The thermally conductive silicone composition of the present invention can be produced by adding a hydrosilylation catalyst as a component (B) and a thermally conductive filler as a component (C) to a liquid silicone containing components (A-1) to (A-4) or components (A-1) to (A-5) and kneading the mixture. However, in order to suppress the advancement of the crosslinking reaction before the use of the thermally conductive silicone composition, for example, it is preferable to mix the polymer components other than the component (A-4) among the polymer components constituting the liquid silicone, add the thermally conductive filler as the component (C) little by little thereto and knead the mixture, and then divide the kneaded product into two, add the hydrosilylation catalyst as the component (B) to one side as agent A, and add the component (A-4) to the other side as agent B, and mix the agents A and B at the time of use or immediately before use. The cured product of the thermally conductive silicone composition can be obtained by curing the thermally conductive silicone composition at room temperature or by curing it by heating.

[0082] Example

[0083] The present invention is described in detail below based on examples and comparative examples in which a thermally conductive silicone composition and a cured product thereof were actually manufactured and evaluated. As evaluation items, the degree of plasticization was measured for the physical properties of the thermally conductive silicone composition (uncured physical properties), and the hardness, thermal resistance change rate, and thermal conductivity were measured for the physical properties of the cured product (cured physical properties).

[0084] <Method for producing thermally conductive silicone composition and cured product>

[0085] In the examples and comparative examples, a thermally conductive silicone composition and a cured product thereof were prepared as follows. First, the polymer components other than the component (A-4) in the liquid silicone were mixed, and the thermally conductive filler and the surface treatment agent as the component (C) were added little by little thereto, and the mixture was heated and kneaded at 150°C in a 600cc Banbury mixer. After the obtained composition was cooled, it was divided into two, and a hydrosilylation catalyst as the component (B) was added to one side as the agent A, and the component (A-4) was added to the other side as the agent B. Thereafter, the agents A and B were mixed in a vacuum mixer while being vacuum degassed, and then filled into a mold, and heated and cured at 23°C for 24 hours or at 90°C for 30 minutes to obtain a cured product.

[0086] <Evaluation method of thermally conductive silicone composition and cured product thereof>

[0087] (1) Plasticity determination method

[0088] The plasticization degree of the thermally conductive silicone composition was measured as follows: 2 cm 2 of each of the A and B agents were collected. 3 , measured using a Williams plasticometer (manufactured by Toyo Seiki Seisaku-sho, Ltd.) in accordance with JIS K6249. Under an environment of 23±2°C, the values ​​of Agent A and Agent B were measured 5 minutes after the load was applied. Thereafter, the average value of the plasticization degree of Agent A and the plasticization degree of Agent B was set as the plasticization degree of the thermally conductive silicone composition. The smaller the value of the plasticization degree, the lower the viscosity of the composition.

[0089] (2) Hardness measurement method

[0090] The above-mentioned manufacturing method was used to manufacture a cured product of 100 mm×100 mm×10 mm thick and used as a test piece. After that, the test piece was conditioned in an environment of 23±2°C and measured using an Asker C hardness tester (manufactured by Kobunsu Keiki Co., Ltd.) in accordance with JIS K7312. At this time, the maximum value after pressing the hardness tester was used as the hardness value.

[0091] (3) Thermal resistance change rate determination method

[0092] A thermally conductive silicone composition was formed into a thickness of 2 mm between two circular plates with a diameter of 50 mm and a thickness of 0.3 mm, and cured to form a test piece. A circular plate made of stainless steel (SUS304) was used as the circular plate. The test piece has a structure in which the cured product is sandwiched between two circular plates. Thereafter, the test piece was left to stand in a constant temperature bath at 150°C for 500 hours. In accordance with ASTME1530, the thermal resistance at 23°C before and after the test was measured using a thermal conductivity measuring device DTC-300 (manufactured by TA INSTRUMENTS JAPAN Co., Ltd.). The thermal resistance measured here is the thermal resistance of the entire test piece consisting of two stainless steel plates and the cured product sandwiched therebetween. When the thermal resistance before standing at 150°C for 500 hours is set to R0 and the thermal resistance after standing is set to R1, the thermal resistance change rate ΔR is expressed by the following formula (7).

[0093] ΔR=((R1-R0) / R0)×100(%)(7)

[0094] (4) Thermal conductivity measurement method

[0095] A cured product of 100 mm × 100 mm × 10 mm thickness was manufactured using the above-mentioned manufacturing method and used as a test piece. Afterwards, the surface of the test piece was covered with plastic wrap (manufactured by Ube Film Co., Ltd.) while being careful not to trap bubbles, so that the test piece was stabilized at 23±2°C. The test piece wrapped with plastic wrap was placed on a reference plate (manufactured by Kyoto Electronics Co., Ltd., material: zirconium oxide, thermal conductivity: 3.36 W / m·K), and the thermal conductivity was measured by connecting the probe PD-13 (manufactured by Kyoto Electronics Co., Ltd.) to the thermal conductivity measuring device QTM-500 (manufactured by Kyoto Electronics Co., Ltd.). The current value is set to I 2 =9.000A 2 , the measurement time is set to 60 seconds.

[0096] (5) Minimum value of mean square error E min And the calculation method of the value a0 of the corresponding coefficient a

[0097] When considering the cumulative particle size distribution, the particle size P at the starting point is set to 0.010 μm, the particle size Q at the end point is set to 316 μm, and R is set to 46. At this time, k is k≈1.259 according to equations (3) and (4). Then, the mean square error E is calculated based on equation (5), and the minimum value E of the mean square error E is calculated. min and the minimum value E min The corresponding value of coefficient a is a0.

[0098] [Example 1]

[0099] In the production of the thermally conductive silicone composition, a dimethylpolysiloxane having vinyl groups at both ends of the molecular chain (DMS-V21, viscosity 100 cSt, manufactured by Gelest, Inc.) was used as the (A-1) component, a dimethylpolysiloxane having vinyl groups only at one end of the molecular chain (RH-Vi305B, viscosity 1000 cSt, manufactured by Zhejiang Runhe Silicone New Material Co., Ltd.) was used as the (A-2) component, a cyclic siloxane having four vinyl groups in the side chain of the molecular chain, namely, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane (manufactured by Sigma-Aldrich Co. LLC) was used as the (A-3) component, and a dimethylpolysiloxane having silicon-bonded hydrogen atoms at both ends of the molecular chain (FLD620V20, viscosity 20 mm 2 / s, manufactured by Elkem Japan Co., Ltd.) as the (A-4) component, and platinum (0)-2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane complex (SIP6832.2, manufactured by Gelest, Inc.) as the (B) component was used as a platinum catalyst. In addition, as the (C) component, three types of thermally conductive fillers were used: aluminum hydroxide with an average particle size of 54 μm (BW53, manufactured by Nippon Light Metal Co., Ltd.), aluminum hydroxide with an average particle size of 10 μm (BW103, manufactured by Nippon Light Metal Co., Ltd.), and aluminum hydroxide with an average particle size of 1 μm (BF013, manufactured by Nippon Light Metal Co., Ltd.), and these fillers were added at the mixing ratios shown in Table 1. As a surface treatment agent for the thermally conductive filler, octyltriethoxysilane (Silquest A-137, manufactured by Momentive Performance Materials Japan Co., Ltd.) was used at the mixing amounts shown in Table 1. It should be noted that, although dimethylpolysiloxane having silicon-bonded hydrogen atoms at both ends of the molecular chain is used as the (A-4) component here, since it is dimethylpolysiloxane and has silicon-bonded hydrogen atoms at both ends of the molecular chain, it can be said that this component is an organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at the ends of the molecular chain and having no silicon-bonded hydrogen atoms in the side chains of the molecular chain.

[0100] As shown in Table 1, in the thermally conductive silicone composition of Example 1, the ratio of the molar number of hydrogen atoms bonded to silicon atoms in the formulated liquid silicone to the molar number of alkenyl groups is 1.0, and the volume percentage of the thermally conductive filler is 69.5% by volume. In addition, the cumulative 25% particle size (D25) calculated on a volume basis based on the particle size distribution and the blending ratio of each thermally conductive filler is 8 μm, the cumulative 50% particle size (D50) is 27 μm, and the cumulative 75% particle size (D75) is 59 μm. The mean square error E calculated using formula (5) reaches a minimum when the parameter (coefficient) a is 9.6 (i.e., a0=9.6). The minimum value of the mean square error E at this time is E min As shown in Table 1, the plasticity of the obtained thermally conductive silicone composition is as low as 28, the hardness and thermal resistance change rate of the cured product are 20 and +2%, respectively, both of which are low, and the thermal conductivity of the cured product is 2.8 W / m·K. These values ​​are satisfactory for a thermally conductive silicone composition.

[0101] [Examples 2 to 6]

[0102] The thermally conductive silicone composition was produced and evaluated in the same manner as in Example 1 except that the addition ratio of the thermally conductive filler was changed.

[0103] [Example 7]

[0104] In the preparation of the thermally conductive silicone composition, a dimethylpolysiloxane having vinyl groups at both ends of the molecular chain (DMS-V31, viscosity 1000 cSt, manufactured by Gelest, Inc.) was used as the (A-1) component, a dimethylpolysiloxane having vinyl groups at one end of the molecular chain (MCR-V25, viscosity 500 cSt, manufactured by Gelest, Inc.) was used as the (A-2) component, a cyclic siloxane having four vinyl groups in the side chain of the molecular chain, namely, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane (manufactured by Sigma-Aldrich Co. LLC) was used as the (A-3) component, and a dimethylpolysiloxane having silicon-bonded hydrogen atoms at both ends of the molecular chain (FLD620V20, viscosity 20 mm 2 / s, manufactured by Elkem Japan Co., Ltd.) as the component (A-4), dimethyl polysiloxane having no reactive functional group (KF-96-100CS, viscosity 100 cSt, manufactured by Shin-Etsu Chemical Co., Ltd.) as the component (A-5), and platinum (0)-1,3-divinyltetramethyldisiloxane complex (P2075, manufactured by Tokyo Chemical Industry Co., Ltd.) as the component (B). The same substances as those in Example 1 were used as the thermally conductive filler and the surface treatment agent in the amounts shown in Table 1. Thereafter, the evaluation was performed in the same manner as in Example 1. The results are shown in Table 1.

[0105] [Examples 8-9]

[0106] A thermally conductive silicone composition was produced and evaluated in the same manner as in Example 7 except that the amounts of the thermally conductive filler and the surface treatment agent as the component (C) were increased as shown in Table 1 compared to those in Example 7. The results are shown in Table 1.

[0107] [Example 10]

[0108] A thermally conductive silicone composition was prepared and evaluated in the same manner as in Example 9 except that the amount of the cyclic siloxane having four vinyl groups in the molecular chain side chain as the component (A-3) and the amount of the thermally conductive filler as the component (C) were reduced compared to Example 9 as shown in Table 1. The results are shown in Table 1.

[0109] [Example 11]

[0110] A thermally conductive silicone composition was produced and evaluated in the same manner as in Example 10 except that the amount of the cyclic siloxane having four vinyl groups in the molecular chain side chain as the component (A-3) was increased as compared with Example 10 as shown in Table 1. The results are shown in Table 1.

[0111] [Example 12]

[0112] In Example 1, a thermally conductive silicone composition was prepared and evaluated by changing the blending amount of each component so that the silicon-bonded hydrogen atom was 1.6 mol per 1 mol of vinyl groups as alkenyl groups contained in the liquid silicone.

[0113] [Example 13]

[0114] In Example 1, a thermally conductive silicone composition was prepared and evaluated by changing the blending amount of each component so that the silicon-bonded hydrogen atom was 0.6 mol per 1 mol of vinyl groups as alkenyl groups contained in the liquid silicone.

[0115] [Examples 14-15]

[0116] Using zinc oxide as the thermally conductive filler of the component (C), a thermally conductive silicone composition was produced and evaluated in the same manner as in Example 7. The thermally conductive fillers used were zinc oxide having an average particle size of 80 μm (large particle size zinc oxide (1), manufactured by Hakusui Tech Co., Ltd.), zinc oxide having an average particle size of 10 μm (calcined zinc oxide, manufactured by Hakusui Tech Co., Ltd.), and zinc oxide having an average particle size of 1 μm (zinc oxide type 1, manufactured by Mitsui Mining & Smelting Co., Ltd.), and the blending amounts of the components were as shown in Table 1. The evaluation results are shown in Table 1.

[0117] [Example 16]

[0118] The same liquid silicone and hydrosilylation catalyst as component (B) were used in the same amounts as those used in Example 1, and a thermally conductive silicone composition was produced in the same manner as in Example 1. As the thermally conductive filler as component (C), three types of aluminum hydroxide (SB93, manufactured by Nippon Light Metal Co., Ltd.) with an average particle size of 105 μm, aluminum hydroxide (BW103, manufactured by Nippon Light Metal Co., Ltd.) with an average particle size of 10 μm, and aluminum hydroxide (BF013, manufactured by Nippon Light Metal Co., Ltd.) with an average particle size of 1 μm were used, and these fillers were added in the mixing ratios described in Table 1. In addition, the same surface treatment agent as in Example 1 was used in the same amounts as in Example 1 as for the thermally conductive filler. The obtained thermally conductive silicone composition was evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0119] [Example 17]

[0120] A thermally conductive silicone composition was produced and evaluated in the same manner as in Example 16 except that the blending amounts of the thermally conductive filler and the thermally conductive filler surface treatment agent were changed.

[0121] [Comparative Examples 1 to 3]

[0122] A thermally conductive silicone composition equivalent to the thermally conductive silicone gel composition disclosed in Patent Document 1 was produced. Dimethylpolysiloxane (SF3000EDK001, viscosity 1000 cSt, manufactured by KCC Corporation) having vinyl groups at both ends of the molecular chain and methylhydrogenpolysiloxane (HMS-151, manufactured by Gelest, Inc.) having four silicon-bonded hydrogen atoms in the molecular chain side chain were used as liquid silicone, platinum (0)-1,3-divinyltetramethyldisiloxane complex (P2075, manufactured by Tokyo Chemical Industry Co., Ltd.) as a platinum catalyst was used as a hydrosilylation catalyst, and the thermally conductive filler and surface treatment agent were the same as those used in Example 1. The blending amounts are shown in Table 1. The obtained thermally conductive silicone composition was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0123] The thermal conductivity of the thermally conductive silicone composition of the comparative example is equal to or slightly lower than that of the thermally conductive silicone composition of the example. The minimum value of the mean square error E is min The plasticization degree is high (i.e., the viscosity is high), and the hardness of the cured product is also high. If the methyl hydrogen polysiloxane having 4 silicon-bonded hydrogen atoms in the side chain of the molecular chain is used to achieve low viscosity and low hardness, the amount of silicon-bonded hydrogen atoms remaining in the cured product increases, and the thermal resistance change rate of the cured product increases. Compared with Comparative Examples 1 and 2, Comparative Example 3 reduces the amount of methyl hydrogen polysiloxane having 4 silicon-bonded hydrogen atoms in the side chain of the molecular chain, and the thermal resistance change rate of the cured product is also lower than that of Comparative Examples 1 and 2, but the hardness of the cured product increases.

[0124] By comparing the examples with the comparative examples, it can be seen that the thermally conductive silicone composition according to the present invention has good thermal conductivity, low plasticity, low viscosity, and low hardness and thermal resistance change rate in its cured product. That is, according to the present invention, it is possible to obtain a thermally conductive silicone composition having a thermal conductivity equal to or higher than that of a conventional thermally conductive silicone composition, low viscosity, and low hardness and thermal resistance change rate in its cured product.

[0125]

[0126]

[0127]

[0128]

[0129] Description of Reference Numerals

[0130] 11: matrix, 12-14: thermally conductive fillers.

Claims

1. A thermally conductive silicone composition comprising: A-1: an organopolysiloxane having alkenyl groups at both ends of the molecular chain; A-2: an organopolysiloxane having an alkenyl group at one end of the molecular chain and having no reactive functional group at the other end; A-3: an organopolysiloxane having at least 3 alkenyl groups in the molecule; A-4: an organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at the molecular chain terminals and no silicon-bonded hydrogen atoms at the molecular chain side chains; B: a hydrosilylation catalyst; and C: thermal conductive filler, The thermally conductive silicone composition is liquid silicone and has curability.

2. The thermally conductive silicone composition according to claim 1, wherein The liquid silicone comprises an organopolysiloxane represented by the following general formula (1): 。 3. The thermally conductive silicone composition according to claim 1 or 2, wherein: The thermally conductive filler includes at least one of aluminum hydroxide and zinc oxide.

4. The thermally conductive silicone composition according to claim 3, wherein: The number of particle sizes at the calculation points of the cumulative frequency in the cumulative particle size distribution based on the volume of the thermally conductive filler is defined as R, the particle sizes of the thermally conductive filler that are the smallest and the largest among the particle sizes at the calculation points of the cumulative frequency are defined as P and Q, respectively, and the particle size of the thermally conductive filler at the nth calculation point determined so as to satisfy the following equations (a1) and (a2) is defined as x. n , the cumulative particle size distribution and the particle size x n The cumulative frequency of the corresponding particle size of the thermal conductive filler on a volume basis is set as c n When P, Q and x n The unit is μm, n is an integer satisfying 1≤n≤R, and c n In %, The minimum value E of the mean square error E expressed by the following formula (a3) min and the minimum value E min The corresponding coefficient a0 satisfies: 0≤E min ≤45 and 5.7≤a0≤13.0; x n =k n-1 P (a1) x R =Q (a2) 。 5. The thermally conductive silicone composition according to claim 3, wherein: The thermally conductive filler accounts for 68.0 volume % or more and 75.0 volume % or less in the thermally conductive silicone composition.

6. A cured product obtained by curing the thermally conductive silicone composition according to claim 1 or 2 by a hydrosilylation reaction.

Citation Information

Patent Citations

  • Thermally-conductive silicone gel composition, thermally-conductive member, and heat dissipation structure

    WO2019021824A1